HT update: spotlight on estradiol/norethindrone acetate combination therapy - Colleen L Casey (Dove Medical Press, 2008)
Colleen L Casey, Christine A MurrayUniversity of Vermont, Department of Obstetrics and Gynecology, Division of Reproductive Endocrinology and Infertility, Burlington, VT, USAAbstract: The goal of postmenopausal hormone therapy is to alleviate the symptoms that are associated with the loss of estrogen. Many formulations of estrogen and progestin are available, depending on the needs and circumstances of each individual woman. For postmenopausal women, the choice of whether or not to begin therapy requires knowledge of the risks and benefits of estrogen and/or progestin replacement. The purpose of this review is to describe the risks and benefits of hormonal therapy, focusing on estradiol/norethindrone acetate combination therapy.Keywords: postmenopausal hormone therapy, norethindrone acetate, estradiol